(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
Food products for mass consumption include products that play a key role in meeting the basic physiological needs of a person in vital elements, energy and liquid. The use of these products is mandatory for a healthy diet and should be part of a daily balanced menu. One of the main technological aspects of the production of mass consumption products is the use of modern equipment, which has advanced engineering solutions and meets the high requirements of energy saving and automation. The use of automated production lines is the basis of innovation in the food industry, as they allow mass production with minimal manual labor. Such lines are equipped with robotic systems and can perform various operations. In order to ensure the safety, quality, environmental friendliness and efficiency of the considered and other latest developments, in particular for products of mass consumption, it is important to implement the latest engineering solutions in the equipment. These solutions are implemented in the projects of technological production lines. The design of the technological line for the production of boiled sausages has been completed. The line is automated. Electric contact heating in the unit included in the line occurs due to the electrical conductivity of the raw material, and consists in the conversion of electrical energy into thermal energy directly in a conductive medium. One of the important advantages of this method is uniform heating of the product throughout the volume. The production line of mayonnaise is also given. The main advantages of the line are the ability to automatically adjust the recipe for stable product quality; implementation of low-temperature emulsification, which allows you to preserve texture and taste. Microfiltration and water purification allows you to purify water before adding it to mayonnaise, which significantly improves its taste properties. The use of modern mixers and emulsifiers reduces energy consumption by 15-20% compared to analogues without loss of productivity, helping to reduce production costs and environmental impact. Recycling and waste reduction are also implemented in the line: the system of collection and processing of production waste allows to reduce the amount of garbage. A technological line for the production of pasteurized milk has been developed. This line has a quality monitoring system that allows you to quickly identify and correct deviations from the norm. Automation of processes on the line is realized by the introduction of robotic systems for such processes as pasteurization, packaging and equipment washing. This increases efficiency and reduces staff work. The use of energy from renewable sources such as solar panels during production to provide energy for production enables the manufacturer to be autonomous and independent of suppliers. The application of nanomaterials to improve the packaging of dairy products in the line provides a longer shelf life and reduces product losses.